ON TERNARY QUADRATIC DIOPHANTINE EQUATION 5(x2 +y2 )-6xy=196z2 - Gopalan, M.A.; Vidhyalakshm, S.; Rajalakshmi, U.K. (IJRDO -JOURNAL OF MATHEMATICS, 2017)
The ternary homogeneous quadratic equation given by 5(x2 +y2)-6xy=196z2 representing a cone is analysed for its non-zero distinct integers solutions. A few interesting relations between the solutions and special polygonal numbers are presented.